Пpедикативные выpaжeния обозначающие зритeльный процесс/действие - Усонене, Аурелия (Kalbotyra, 1987)
The paper is concerned exclusively with the semantic peculiarities of the predicates denoting visual process/action. Some specific lexical differences of such verbs of vision as LOOK, GLANCE, OBSERVE and WATCH are determined. Besides, the occasional use of the verb SEE in the Continuous form and its status is discussed.